2002
DOI: 10.1038/nrn843
|View full text |Cite
|
Sign up to set email alerts
|

The musician's brain as a model of neuroplasticity

Abstract: Studies of experience-driven neuroplasticity at the behavioural, ensemble, cellular and molecular levels have shown that the structure and significance of the eliciting stimulus can determine the neural changes that result. Studying such effects in humans is difficult, but professional musicians represent an ideal model in which to investigate plastic changes in the human brain. There are two advantages to studying plasticity in musicians: the complexity of the eliciting stimulus music and the extent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
504
1
18

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(551 citation statements)
references
References 66 publications
28
504
1
18
Order By: Relevance
“…It is known that musical expertise encompasses both anatomical and functional changes in the brain (Münte et al, 2002), and contributes to improved WM performance (Gaab, Gaser, & Schlaug, 2006). Recent neuroimaging evidence provided by Schulze, Mueller, and Koelsch (2011) has supported this view.…”
Section: Neuroimaging Studies Of Music-related Working Memorymentioning
confidence: 96%
See 1 more Smart Citation
“…It is known that musical expertise encompasses both anatomical and functional changes in the brain (Münte et al, 2002), and contributes to improved WM performance (Gaab, Gaser, & Schlaug, 2006). Recent neuroimaging evidence provided by Schulze, Mueller, and Koelsch (2011) has supported this view.…”
Section: Neuroimaging Studies Of Music-related Working Memorymentioning
confidence: 96%
“…Moreover, musicians -experts in the musical domain-exhibit functional and structural changes in the brain, what also has driven music into a device for studying brain plasticity (Hyde, Lerch, Norton, Forgeard, Winner, & Evans, 2009;Schlaug, 2006;Münte, Altenmüller, & Jäncke, 2002).…”
Section: Cognitive Neuroscience Of Musicmentioning
confidence: 99%
“…A later scan, three months later, after a period during which they had not practiced and no longer possessed those skills, showed that the enlargement had regressed. In career musicians, however, who continue to practice assiduously for years, such changes, as in string players, persist (Munte et al, 2002).…”
Section: Does Neurogenesis Occur In Human Adults?mentioning
confidence: 99%
“…Accomplished and famous musicians usually began with musical training in early childhood, practicing several hours a day. Professional musicians represent therefore an ideal model for the study of training-induced plastic changes in the human brain (Münte et al, 2002;Schlaug, 2001). …”
mentioning
confidence: 99%